On the emergence of social conformity - Edward Cartwright (University of Kent, Department of Economics, 2005)
We consider a dynamic model of conformity that permits both a conformist and non-conformist equilibrium. We provide conditions under which conformity can 'invade' a population. More precisely, starting from a non-conformist equilibrium, we show that the conformity of an arbitrarily small proportion of the population can lead to the spread of conformism and the ultimate emergence of the conformist equilibrium. This occurs independently of whether or not the non-conformist equilibrium Pareto dominates the conformist equilibrium.
Keywords: C70; D01; C72; 330; Conformity; best reply; coordination; norm; Dynamisches Modell; Soziale Norm